2017
DOI: 10.1021/acsomega.7b01459
|View full text |Cite
|
Sign up to set email alerts
|

Developing Neolignans as Proangiogenic Agents: Stereoselective Total Syntheses and Preliminary Biological Evaluations of the Four Guaiacylglycerol 8-O-4′-Coniferyl Ethers

Abstract: Stereoselective total syntheses of the four stereoisomeric forms of guaiacylglycerol 8-O-4′-coniferyl ether, viz., compounds 1, ent-1, 2, and ent-2, have been established. The key step involves an Evans/Seebach auxiliary-controlled and syn-selective aldol process followed, in the reaction sequences leading to the anti-compounds, by a Mitsunobu reaction involving a benzylic alcohol residue. The proangiogenic properties of the synthetic materials were evaluated in a human microvascular endothelial cell tubule fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
1
0
2
Order By: Relevance
“…In a parallel study the four stereoisomers of GGCE were synthesised and a paper describing the synthesis of these four compounds was recently published [ 57 ]. It was found that all four stereoisomers could enhance endothelial cell tube formation, but e GGCE was the least active.…”
Section: Discussionmentioning
confidence: 99%
“…In a parallel study the four stereoisomers of GGCE were synthesised and a paper describing the synthesis of these four compounds was recently published [ 57 ]. It was found that all four stereoisomers could enhance endothelial cell tube formation, but e GGCE was the least active.…”
Section: Discussionmentioning
confidence: 99%
“…O solvente foi removido sob pressão reduzida, o resíduo foi diluído com água e adicionado ao funil de separação e o produto foi extraído com acetato de etila (3 x 50 mL). A camada aquosa foi então resfriada a 0ºC, acidificado a pH 2-3 com uma solução de HCl 2N, levando a um sólido branco que foi filtrado e seco segundo a metodologia descrita por Buckler et al (2017) [35].…”
Section: áCido 2-(4-alil-2-metoxifenoxi)acético (5)unclassified
“…A validação dos parâmetros utilizados no docking molecular foi realizada através do estudo de re-docking realizado com o ligante co-cristalizado da enzima em questão, o posaconazol, sendo considerados efetivos os parâmetros capazes de reproduzir satisfatoriamente (expressar valores de Root Mean Standard Deviation -RMSD ≤ 2 Å) a conformação desse ligante constante no complexo obtido por cristalografia. [35]. No entanto, a literatura não descreve a síntese do composto 6.…”
Section: Modelagem Molecularunclassified